Safety and feasibility of cardiopulmonary exercise testing in head and neck cancer survivors. (27th December 2022) - Midgley, Adrian W.; Levy, Andrew R.; Cunha, Felipe A.; Key, Angela; Patterson, Joanne M.; Rogers, Simon N.
Abstract: Purpose: Assess safety and feasibility of the cardiopulmonary exercise test (CPET) for evaluating head and neck cancer (HaNC) survivors. Also compare their cardiorespiratory fitness to age and sex‐matched norms and establish current physical activity levels. Methods: Fifty HaNC survivors [29 male; mean ( SD ) age, 62 (8) years], who had completed treatment up to 1 year previously, were recruited. Participants performed a CPET on a cycle ergometer to symptom‐limited tolerance. Participants completed a questionnaire to report contributory factors they perceived as influencing test termination. Physical activity levels were determined using a self‐reported physical activity questionnaire. Results: Three participants did not complete the CPET because (1) poor fitting mouthpiece and naso‐oral mask due to facial disfiguration from surgery; (2) knee pain elicited by cycling; and (3) early CPET termination due to electrocardiogram artefacts. Participants reached a mean peak oxygen uptake that was 34% lower than predicted and the mean ( SD ) CPET duration of 7:52 (2:29) min:s was significantly lower than the target test duration of 10 min ( p < 0.001). Leg muscle aches and/or breathing discomfort were major contributory factors influencing test termination for 78% of participants, compared to 13% for dry mouth/throat and/or drainage in the mouth/throat. No major adverse events occurred. Participants were categorised as 26% active, 8% moderately active, and 66% insufficiently active. Conclusion: These preliminary data suggest the CPET appears safe and feasible for most HaNC survivors when strict exclusion criteria are applied; however, low levels of cardiorespiratory fitness should be considered when calculating an appropriate ramp rate.